Estudo de sete espécies de Rhodnius (Hemiptera, Reduviidae, Triatominae) por meio de dois genes nucleares e um mitocondrial - Ferreira Filho, Júlio César Rente [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Os membros da subfamília Triatominae são vetores do protozoário Trypanosoma cruzi, agente etiológico da doença de Chagas. Eles compreendem 144 espécies agrupadas em 18 gêneros e são encontrados principalmente nas Américas, desde o sul dos Estados Unidos ao sul da Argentina e Chile. Essencialmente a identificação desses insetos tem sido baseada na descrição comparativa da morfologia de indivíduos adultos incluindo as estruturas da genitália masculina e feminina, aspectos gerais do corpo como cabeça, tórax, antena e coloração, entre outros. Entretanto a distinção por critérios morfológicos apresenta limitações para caracterização de espécies do gênero Rhodnius devido às semelhança entre elas, especialmente entre R. prolixus, R. domesticus, R. robustus, R. neglectus, and R. nasutus, espécies conhecidas como “grupo prolixus”. Nesse estudo as técnicas de biologia molecular, sequenciamento do gene 16S e PCR-RFLP, foram utilizados para caracterização de sete espécies de Rhodnius. Os produtos do sequenciamento do gene 16S das espécies R. brethesi; R. nasutus, R. nasutus, R. neglectus, R. pictipes; R. prolixus, R. robustus, e R. sp geraram alinhamento de 380 pares de bases com 48 sítios polimórficos. A visualização das bandas geradas pelas enzimas de restrição BstUI, HhaI, RsaI and Mbol com as sete amostras de Rhodnius possibilitou distingui-las com exceção de R. prolixus, R. neglectus e R.robustus. Os dois métodos feitos para as mesmas amostras confirmaram a validade da utilização do método PCR-RFLP para identificação de R. brethesi, R. nasutus, R. pictipes e R. sp, uma vez que o gene 16S já é um marcador estabelecido para as espécies de Rhodnius e as duas metodologias apresentaram os mesmos resultados, confirmaram também o trabalho realizado por Naegele et al. 2006 em que a técnica de PCR-RFLP distinguiu R. stale, R. pictipes, R. Prolixus and R. domesticus

The members of the subfamily Triatominae are vectors of the protozoan Trypanosoma cruzi, which is the etiologic agent of Chagas disease. They consist of 144 species grouped into 18 genera and are found mainly in the Americas, from the southern United States to southern Argentina and Chile. Essentialy, the identification of these insects has been based on the comparative description of the morphology of adult specimens, including the structures of both the male and female genitalia, general body features like head, thorax, antennae and color, among others. However, this method is not particularly useful in the characterization of species belonging to the genus Rhodnius because they are very similar morphologically, specially R. prolixus, R. domesticus, R. robustus, R. neglectus, and R. nasutus, which are known as “prolixus complex”. In this study molecular biology techniques, such as sequencing of 16S gene and PCR-RFLP, was used to contribute to the characterization of seven species of Rhodnius. The products of the sequencing of the 16S species R. brethesi; R. nasutus, R. nasutus, R. neglectus, R. pictipes; R. prolixus, R. robustus, and R. sp generated a alingment of 380bp with 48 polymorphic sites. The visualization of the bands arising from the use of restriction enzymes BstUI, HhaI, RsaI and Mbol with samples of seven species of Rhodnius possible to distinguish them except for R. prolixus, R. neglectus and R.robustus. The two methods performed in parallel for the same samples confirmed the validity of using the enzymatic method for specific identification of R. brethesi, R. nasutus, R. pictipes e R. sp, since the 16S gene is already an established marker for it and the two methods showed the same results, confirmed too the work performed by Naegele et al.2006 that the PCR-RFLP technic distinguished R. stale, R. pictipes, R. Prolixus and R. domesticus
Keywords: Rhodnius prolixus; Tripanossomo; Chagas, Doença de; Gene 16S; Trypanosoma